Food and nutrition security data on the World Wide Web - Slack, Alison T. (International Food Policy Research Institute, 1998)
This guide provides the reader with a discussion of the types of data concerning food security indicators that are available via the Internet for individual developing countries on a disaggregated level, and where on the Internet they can be obtained. It provides this information in the context of discussion on "process" versus "outcome indicators" for use in the identification of food insecure areas and vulnerable populations within countries.